Influence of microbially enriched mineral fertilizers on the composition of rhizosphere microorganisms of Thuja occidentalis - Sas Paszt, Lidia; Smolińska, Urszula; Treder, Jadwiga; Szczech, Magdalena; Kowalska, Beata; Trzciński, Paweł; Głuszek, Sławomir; Lisek, Anna; Derkowska, Edyta; Frąc, Mateusz (Polish Journal of Agronomy, 2021)
Rhizosphere is a region of the strongest interactions be- tween plants, soil and microorganisms, which play an important role in plant development. Due to a number of interdependencies, they are main factors determining the health and proper growth of plants. All methods used in agriculture that promote the growth of microbial populations and their biodiversity are beneficial both for cultivated plants and for the environment. Thuja occidentalis cv. Brabant, is a very popular plant in Poland. In the study the effect of mineral fertilizers: Urea, Polifoska 6, Super Fos Dar 40, enriched with beneficial strains of fungi and bacteria, on selected groups of soil microorganisms was evaluated. The fungi Asper- gillus niger and Purpureocillium lilacinum and bacteria Bacillus sp., Bacillus amyloliquefaciens, Paenibacillus polymyxa, which have been shown to have beneficial effects on plant growth in previous works, have been used as additives to bio-fertilizers. The use of mineral fertilizers Urea, Polifoska 6 and Super Fos Dar 40, enriched with selected strains of fungi and bacteria had a beneficial effect on the development of microorganisms in the rhizosphere of the Thuja occidentalis, especially in the second year of research.